Beyond HR : the new science of human capital - Boudreau, John W.; Ramstad, Peter M. (Boston, Mass. : Harvard Business School Pub., 2007)
In Beyond HR: The New Science of Human capital, John Boudreau and Peter Ramstad show you how to do this through a new decisions science-talentship. Through talentship, you move far beyond merely reactive mind-set of planning and budgeting for headcount and hiring and retaining talent.
The essential evolution: personnel, human resources, talentship -- A decision science applied to talent: understanding the necessary components -- The HC BRidge framework: pivot-points in impact, effectiveness, and efficiency -- Impact in strategy analysis: finding the strategy pivot-points -- Impact in organization and talent: linking strategic pivot-points to structures and roles -- Effectiveness in performance and potential: aligning the pivotal interactions and actions through culture and capacity -- Effectiveness in policies and practices: creating the strategic portfolio of talent programs -- Efficiency in organization and talent investments: acquiring and deploying resources to optimize the talent portfolio -- Talent measurement and analytics: beyond measures to the LAMP -- Making talentship work: how the HR evolution becomes a practical reality.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Intellectual capital; Knowledge management; Knowledge workers; Decision making; Human capital; Personnel management; Capital intellectuel; Gestion des connaissances; Travailleurs du savoir; Prise de décision; Ressources humaines; Personnel -- Direction; Personeelsmanagement; Human Capital; Kennismanagement; Humankapital; Intellektuelles Kapital; Wissensmanagement; Decision making; Human capital; Intellectual capital; Knowledge management; Knowledge workers; Personnel management; POLITICAL SCIENCE / Public Affairs & Administration; elektronické knihy; electronic books